Correlation of Folic Intake and Internal Carotid Artery Intima-Media Thickness Changes In Post Ischemic Stroke Patients - Dodik Tugasworo; Dwi Pudjonarko; Latifah Latifah (Chemical Engineering Diponegoro University, 2015)
The thickness of the carotid artery intima media / intima-media thickness (IMT) is one of atherosclerosis markers. Atherosclerosis is one of the causes of ischemic stroke. Some studies suggest that low folate intake is predicted to affect the atherosclerotic process, but this remains controversial. Our objective is to analyze the relationship between folate intake with changes in the internal carotid artery IMT after ischemic stroke patients.The study is one group pretest posttest design with 72 post ischemic stroke subjects from neurology polyclinic of Kariadi Hospital, from June to December 2013. Folate intake was measured by Food Frequency Questionnaire and the internal carotid artery IMT by duplex ultrasonography. Measurements were taken at two periods with 6 months interval. Other factors that affect atherosclerosis consisting of age, obesity, hypertension, dyslipidemia, diabetes mellitus. The analysis in this study using Spearman correlation, chi-square and logistic regression. Resultwas significant if the p value were <0.05.There were 44 male subjects (61.1%) and 28 female subjects (38.9%). The mean age was 61.6 (SD = 7.99) years. The mean intake of folate was 178.10 (SD = 38.875) mg / day. Median serum folic acid level 8.43 (4.96 to 55.01) NML / L. The mean change in ICA IMT was 0.10 (SD = 0.156) mm. Folate intake was not correlated with serum levels of folic acid. Serum folic acid levels are not correlated with changes in the internal carotid artery IMT. There was correlation between the risk factors of age, BMI, hypertension, diabetes and dyslipidemia with changes in the internal carotid artery IMT.